2009
DOI: 10.1194/jlr.m800337-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis, pharmacological characterization, and possible formation in unicellular fungi of 3-hydroxy-anandamide

Abstract: The fungal pathogen Candida albicans transforms arachidonic acid (AA) into 3-hydroxyarachidonic acid [3(R)-HETE], and we investigated if its nonpathogenic and 3(R)-HETE-producing close relative, Dipodascopsis uninucleata, could similarly transform the endocannabinoid/endovanilloid anandamide into 3-hydroxyanandamide (3-HAEA). We found that D. uninucleata converts anandamide into 3-HAEA, and we therefore developed an enantiodivergent synthesis for this compound to study its pharmacological activity. Both enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In conclusion, from the present data, it seems unlikely that 9( S )‐HODE or (+/–)13‐HODE, rather than arachidonic acid derivatives, such as anandamide or 15( S )‐HAEA, are mostly responsible for tonic TRPV1 activity in the spinal cord during inflammatory pain, even accounting for their potentially higher concentrations or the presence of TRPV1‐sensitizing factors. Indeed, other oxidation products of arachidonic acid, such as the fungal metabolite 3‐HETE (De Petrocellis et al ., ), and the P450 arachidonic acid metabolite, 20‐HETE (Wen et al ., ), activate native and heterologously expressed TRPV1 with EC 50 values in the low micromolar range; whereas low nanomolar concentrations of derivatives from the oxidation of docosahexaenoic acid seem instead to act as indirect endogenous inhibitors of TRPV1 and TRPA1 (Park et al ., ). However, when these oxidative metabolites are generated in the periphery in inflammation, they might have different effects at primary afferent nerve terminals, when compared with those observed here on DRG cell bodies or transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, from the present data, it seems unlikely that 9( S )‐HODE or (+/–)13‐HODE, rather than arachidonic acid derivatives, such as anandamide or 15( S )‐HAEA, are mostly responsible for tonic TRPV1 activity in the spinal cord during inflammatory pain, even accounting for their potentially higher concentrations or the presence of TRPV1‐sensitizing factors. Indeed, other oxidation products of arachidonic acid, such as the fungal metabolite 3‐HETE (De Petrocellis et al ., ), and the P450 arachidonic acid metabolite, 20‐HETE (Wen et al ., ), activate native and heterologously expressed TRPV1 with EC 50 values in the low micromolar range; whereas low nanomolar concentrations of derivatives from the oxidation of docosahexaenoic acid seem instead to act as indirect endogenous inhibitors of TRPV1 and TRPA1 (Park et al ., ). However, when these oxidative metabolites are generated in the periphery in inflammation, they might have different effects at primary afferent nerve terminals, when compared with those observed here on DRG cell bodies or transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, cyclization of the chain, as in prostaglandin ethanolamides (prostamides), abolishes activity at both receptor types (Matias et al 2004). By introducing a conformational constraint in the ethanolamine "head" of AEA and N-oleoylethanolamine, we recently demonstrated that the N-alkyl group of these ethanolamides has a different role in their interaction with cannabinoid or TRPV1 receptors (Appendino et al 2009). Interestingly, as reviewed recently (Oz et al 2006), the conformational flexibility of the acyl and N-alkyl chains of acylethanolamide endocannabinoids/endovanilloids allows them to interact also with several other molecular targets.…”
Section: Trpv1mentioning
confidence: 97%
“…C. albicans can also metabolize host arachnoid acid to bi-products that can directly activate nociceptor transient receptor potential cation channel subfamily V member 1(TRPV1) suggesting that multiple pathways of activation may exist. [59]. …”
Section: Innate Immune Response To C Albicansmentioning
confidence: 99%